2008
DOI: 10.1213/ane.0b013e3181684fbb
|View full text |Cite
|
Sign up to set email alerts
|

Sealing of a Tracheoesophageal Fistula Using a Sengstaken-Blakemore Tube for Mechanical Ventilation During General Anesthesia

Abstract: A 78-yr-old man was admitted to our hospital because of repeated episodes of pneumonia. Both fiberoptic bronchoscopy and esophagoscopy revealed a large tracheoesophageal fistula and protrusion of the metal stent from the esophagus into the trachea. Placement of a Dumon stent was planned for sealing this fistula under general anesthesia. Anesthetic management is difficult because of the care needed to prevent aspiration of esophageal contents and diversion of oxygen through the fistula into the stomach from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…More complex fistulas have been managed successfully with bilateral endobronchial intubation [ 14 ], extracorporeal membrane oxygenation [ 15 ], and cardiopulmonary bypass [ 16 ]. Some authors reported sealing the fistula prior to the intervention, using a modified esophageal balloon [ 17 ], or a Sengstaken–Blakemore tube [ 18 ]. Garg et al [ 19 ] reported two cases in children where they sealed the TEF using Fogarty and Foley catheter.…”
Section: Discussionmentioning
confidence: 99%
“…More complex fistulas have been managed successfully with bilateral endobronchial intubation [ 14 ], extracorporeal membrane oxygenation [ 15 ], and cardiopulmonary bypass [ 16 ]. Some authors reported sealing the fistula prior to the intervention, using a modified esophageal balloon [ 17 ], or a Sengstaken–Blakemore tube [ 18 ]. Garg et al [ 19 ] reported two cases in children where they sealed the TEF using Fogarty and Foley catheter.…”
Section: Discussionmentioning
confidence: 99%